2015
DOI: 10.1016/j.atmosenv.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of transportation changes on air quality

Abstract: h i g h l i g h t sEffect of air quality plans on black carbon concentrations has been evaluated. Black carbon concentrations were reduced by limiting traffic to public transport. Reorganization of bus routes and renewal of the bus fleet improve air quality. a b s t r a c t Transport regulation at local level for the abatement of air pollution has gained significant traction in the EU. In this work, we analyze the effect of different transportation changes on air quality in two similarly sized cities: Granada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 38 publications
(48 reference statements)
2
34
0
1
Order By: Relevance
“…Here absolute uncertainties of −20% and +40% were adopted to simulate AAE BC over a range from 0.8 to 1.4 . The relative uncertainty of absorption measurements of the model AE33 is ±5% (Titos et al, 2015).…”
Section: 1029/2018jd029352mentioning
confidence: 99%
“…Here absolute uncertainties of −20% and +40% were adopted to simulate AAE BC over a range from 0.8 to 1.4 . The relative uncertainty of absorption measurements of the model AE33 is ±5% (Titos et al, 2015).…”
Section: 1029/2018jd029352mentioning
confidence: 99%
“…In addition, a new bus line operated by new buses with lower emissions passing through Gran Vía street, GV, was implemented. Titos et al (2015) showed that EBC concentrations were reduced in 37% in GV in the two weeks just after the new system was operational. No changes were observed in other parts of the city like PC or UGR .…”
Section: Effectiveness Of Implemented Pollution Abatement Measuresmentioning
confidence: 99%
“…The total method uncertainty for the aerosol light absorption coefficient inferred from MAAP measurements is around 12% (Petzold and Schönlinner, 2004;Petzold et al, 2005). (Hansen and Novakov, 1984) and AE33 (Drinovec et al, 2015). A complete description of the operating principles of Aethalometers can be found in Hansen (2005) and Drinovec et al (2015).…”
Section: Aerosol Absorption Measurementsmentioning
confidence: 99%
See 2 more Smart Citations